The Effectiveness Of Using Duolingo Application For Students` Grammar Ability In English - Pingki Youlanda, Wariyati (CV. PUSDIKRA MITRA JAYA, 2023)
The purpose of this research is to investigate wheather or not Duolingo can improve students’ grammar ability in English. This research use quantitative method and conducted in VII-B SMP Satria Dharma Perbaungan. In this research, the reasearcher used one class as the sample with total number of 26 students. The data was collected by giving pre-test and post-test as the instruments. The result of this research was calculated by using T-test. The findings showed that the students’ post-test scores was (80,76) it was higher than their pre-test scores (61,73). The result that is showed by using t-test, the scores of tcalculation (8,57) was higher than score of ttable (1,705) at significant level 5%. This finding reveals that Duolingo gives the significant result at 7th grade students of SMP Satria Dharma Perbaungan to increase students grammar ability in English.